Antidumping Investigations and the Pass-Through of Antidumping Duties and Exchange Rates: Reply - Blonigen, Bruce A; Haynes, Stephen E (American Economic Review, 2010)
This reply responds to a comment that correctly identifies an invalid assumption in our original article that antidumping (AD) duties are subtracted from the U.S. price when calculating AD duties in administrative reviews. While this point invalidates our theoretical explanation and empirical evidence on the magnitude of AD duty pass-through, it does not affect our original article's theory or empirical evidence on the magnitude of exchange rate pass-through, or the presence of structural breaks in both the AD duty and exchange-rate pass-through coefficients stemming from AD investigations and orders.